A framework for developing playfulness, experimentation and critical thinking within the concepts of Technological Comprehension and Computational Thinking - Merethe Haahr Francis; Søren Baltzer Rasmusen (University of Huddersfield Press, 2021)
This article draws on insights from cases of researching, developing and teaching Computational Thinking (CT) and Technological Comprehension (TC) within the Arts/Humanities; to show how a guiding framework might enable teaching and learning as a co-operative playful academic community in educational practice. The cases are a research project on implementing Technological Comprehension within the subject of Danish in elementary school (2018-2019); Computational Network Zealand (2019); a Master's course in CT and design processes at Aarhus University (2019-2020). The cases were selected within the context of integrating CT and TC in the educational system of Denmark. The article aims to create a guiding framework for scaffolding pedagogical processes and creating educational design patterns. Through the process of creating Educational design Patterns the educators are supported in creating curriculum development from a bottom-up perspective. This is done through tinkering and playfulness in design collaboratories with a pedagogical foundation submerged in the liberating bildung and critical pedagogy.This article promotes a guiding framework for developing playfulness, experimentation and critical thinking within the concepts of TC and CT.